If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8b + 3(2b + 2) = 11 Reorder the terms: 8b + 3(2 + 2b) = 11 8b + (2 * 3 + 2b * 3) = 11 8b + (6 + 6b) = 11 Reorder the terms: 6 + 8b + 6b = 11 Combine like terms: 8b + 6b = 14b 6 + 14b = 11 Solving 6 + 14b = 11 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 14b = 11 + -6 Combine like terms: 6 + -6 = 0 0 + 14b = 11 + -6 14b = 11 + -6 Combine like terms: 11 + -6 = 5 14b = 5 Divide each side by '14'. b = 0.3571428571 Simplifying b = 0.3571428571
| 8v-12+5v=5v+10-3v | | 7(3x-1)=5+4(x-3) | | -4k-8+11=-3k-12 | | -16x=-8 | | 3x^2+12x-61=0 | | 3x^2+36+105= | | -7+4(3a+1)=-7 | | 8+7x=109 | | 6/5+3/5x=61/30+7/6x+1/6 | | -7x-9y=-3 | | 1/6(6y+12)-9=-1/4(12y-20) | | 7=2x/5 | | 3x+6-x=69 | | 89-(5x+13)=5(x+2)+x | | 5d-2(6d+5)=5-(10+10d) | | 3-2lnx=8 | | -113=7+10x | | 7/6x+3x/5 | | 34=16*x-14 | | 6(3+2x)-1=65 | | a+(b^2)*3c-2d= | | (9ab+7cd)*3e= | | r+0.10=760 | | 9ab+7cd= | | 30=-5/4x | | m=19-5(x-n) | | 5a+4b+3c+4d+3e= | | 5a*4b*3c*4d*3e= | | r/2+0.6r=247 | | 2a-3b=12 | | 8-2(t-1)=t+7 | | 5a*4b*3c= |